Design and clinical application of X-shaped cross-dressing method in rhytidectomy - Mingyu Zhao; Lehao Wu; Qianwen Wang; Tailing Wang; Jiaqi Wang (Advances in Oral and Maxillofacial Surgery, 2023)
Objective: To investigate the effect of “X''-shaped cross-compression dressing of nasal root in rhytidectomy surgery. Methods: From 2019.01 to 2022.02, 60 patients with high SMAS facelift in our department were selected to undergo “X''-shaped cross compression bandaging of the nasal root, and the incidence of postoperative hematoma and skin necrosis were counted. Results: There were two small-scale hematomas, and no flap infection and skin necrosis were observed postoperatively. Conclusion: Nasal “X''-shaped cross-compression bandaging method is reliable. It can effectively prevent the occurrence of postoperative hematoma and other complications and significantly improve patients' comfort. Evidence based medicine(ebm) level: IV.